Base case (n = 1):
• On the left side: 1/(1×2) = 1/2
• On the right side: 1/(1 + 1) = 1/2
Induction hypothesis: Assume the statement is true for n = k ; that is,
1/(1×2) + 1/(2×3) + … + 1/(k × (k + 1))) = k/(k + 1)
Inductive step (n = k + 1):
1/(1×2) + 1/(2×3) + … + 1/(k × (k + 1))) + 1/((k + 1) × (k + 2)))
= k/(k + 1) + 1/((k + 1) × (k + 2))
= (k × (k + 2) + 1) / ((k + 1) × (k + 2))
= (k ² + 2k + 1) / ((k + 1) × (k + 2))
= (k + 1)² / ((k + 1) × (k + 2))
= (k + 1) / (k + 2)
and this is what we wanted to show.